Clinical and radiological classification of otosclerosis - Kryukov, A I; Garov, E V; Zelikovich, E I; Sidorina, N G; Zagorskaya, E E; Fedorova, O V; Zelenkova, V N; Kurilenkov, G V; Moseikina, L A; Kaloshina, A S; Kiselyus, V E; Sudarev, P A; et al. (Vestnik otorinolaringologii, 2023)
The article presents various classifications of forms of otosclerosis (OS), which change with the development of diagnostic methods. At the same time, according to the literature, a unified OS classification has not yet been adopted. All existing classifications are imperfect to some extent. The classification of clinical forms of OS according to TPA data makes it possible to determine the indications for surgical treatment and to suggest its possible effect, but not the localization of OS foci. X-ray classifications of localization of OS foci indicate their diversity, distribution, and do not always correlate with the type of hearing loss. At the same time, modern diagnostics of OS should be based on audiological data, localization of foci and their density according to the results of X-ray methods of examination. Based on the examination and treatment of 1532 patients with various forms of OS, a modern clinical and radiological classification of the disease is proposed, based precisely on these provisions. This classification, in our opinion, will improve the quality of diagnosis of various forms of OS, will allow to differentiate the tactics of treating patients with this disease to stabilize hearing loss, indications for surgical treatment, suggest its effectiveness with a reduction in the risk of surgical failures and possible further rehabilitation of the patient.